Role of Islamic Religious Education in Shaping Religious Moderation in the Era of Digitalization - Lubis (Information Technology Education Journal, 2025)
The digital era presents both opportunities and challenges for religious education, particularly with the increasing spread of intolerance and radicalism through online platforms. This study aims to analyze the role of Islamic Religious Education (PAI) in fostering religious moderation in the digital era, using a field study at MAN Kota Palopo. Employing a qualitative approach, data were collected through interviews, observations, and documentation involving PAI teachers, students, and the madrasah head. The analysis followed Miles and Huberman’s model of data reduction, presentation, and conclusion drawing. The findings reveal that the PAI curriculum has been systematically designed to integrate moderation values such as tolerance, justice, and respect for diversity. Teachers act not only as facilitators and role models but also utilize digital media to strengthen interactive and contextual learning. Students demonstrate openness, active participation in discussions, and the ability to critically filter digital content. Institutional support, including digital literacy programs, technological facilities, and character-building initiatives, further reinforces the internalization of moderation values. The novelty of this study lies in its integration of religious moderation with digital literacy practices, highlighting how PAI can address contemporary challenges while maintaining relevance to 21st-century education. The study concludes that fostering moderation in the digital age requires synergy between curriculum, teachers, students, and school policies, with digital literacy serving as a key strategy for sustainable religious education.